2020
DOI: 10.1371/journal.pone.0232351
|View full text |Cite
|
Sign up to set email alerts
|

Identification of developmental disorders including autism spectrum disorder using salivary miRNAs in children from Bosnia and Herzegovina

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by major social, communication and behavioural challenges. The cause of ASD is still unclear and it is assumed that environmental, genetic and epigenetic factors influence the risk of ASD occurrence. MicroRNAs (miRNAs) are short 21-25 nucleotide long RNA molecules which post-transcriptionally regulate gene expression. MiRNAs play an important role in central nervous system development; therefore, dysregulation of miRNAs is connected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 78 publications
(92 reference statements)
0
29
1
Order By: Relevance
“…Hicks et al concluded that the differentially expressed salivary miRNAs in children with ASD can affect their behavior and also identify ASD patients and normal individuals [ 136 ]. Through the miRNA expression profiling of 14 autistic salivary samples by qRT-PCR, Sehovic et al found that six salivary miRNAs were differentially expressed in ASD children and TD children, and also identified five miRNAs, including miR-7-5p, miR-23a-3p, miR-32-5p, miR-140-3p, and miR-628-5p, as potential biomarkers of ASD children [ 137 ]. As shown in Figure 2 b, there are no common dysregulated miRNAs in the two studies of saliva biomarkers [ 136 , 137 ], which may be caused by the different age distributions of the saliva samples.…”
Section: Mirnas As Potential Diagnostic Biomarkers Of Asdmentioning
confidence: 99%
See 2 more Smart Citations
“…Hicks et al concluded that the differentially expressed salivary miRNAs in children with ASD can affect their behavior and also identify ASD patients and normal individuals [ 136 ]. Through the miRNA expression profiling of 14 autistic salivary samples by qRT-PCR, Sehovic et al found that six salivary miRNAs were differentially expressed in ASD children and TD children, and also identified five miRNAs, including miR-7-5p, miR-23a-3p, miR-32-5p, miR-140-3p, and miR-628-5p, as potential biomarkers of ASD children [ 137 ]. As shown in Figure 2 b, there are no common dysregulated miRNAs in the two studies of saliva biomarkers [ 136 , 137 ], which may be caused by the different age distributions of the saliva samples.…”
Section: Mirnas As Potential Diagnostic Biomarkers Of Asdmentioning
confidence: 99%
“…Through the miRNA expression profiling of 14 autistic salivary samples by qRT-PCR, Sehovic et al found that six salivary miRNAs were differentially expressed in ASD children and TD children, and also identified five miRNAs, including miR-7-5p, miR-23a-3p, miR-32-5p, miR-140-3p, and miR-628-5p, as potential biomarkers of ASD children [ 137 ]. As shown in Figure 2 b, there are no common dysregulated miRNAs in the two studies of saliva biomarkers [ 136 , 137 ], which may be caused by the different age distributions of the saliva samples. Hicks et al used samples from 2–6 year olds [ 136 ], while Sehovic et al used samples from children with an average age of 5.8 years [ 137 ].…”
Section: Mirnas As Potential Diagnostic Biomarkers Of Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that a subset of salivary miRNAs is also associated with measures of adaptive and ASD behaviors. In addition to the RNA sequencing approach, a qRT-PCR based analysis of salivary miRNA was published by Sehovic et al in 2020 [ 74 ]. Using this relatively cheap method available in most diagnostic laboratories, fourteen miRNAs were analyzed in typically developing children and children with some type of developmental disorder including ASD.…”
Section: Saliva In Asd Researchmentioning
confidence: 99%
“…For example, miR-146b-5p, piR-6463, piR-24085, and miR-148a-5p, associated with behavior parameters and/or change over time in a longitudinal study [ 75 ], were also included in a diagnostic panel [ 71 ] or identified by RNA sequencing [ 73 ]. In addition, miR-23a-3p was similarly identified as overexpressed by RNA sequencing and by qPCR [ 66 , 74 ]. These findings provide pieces of preliminary evidence that RNAs represent promising markers for monitoring developmental trajectory, therapeutic efficiency, and prognosis of ASD.…”
Section: Saliva In Asd Researchmentioning
confidence: 99%